Current and prospective strategies in the management of Glioblastoma - Wołodkiewicz, Hanna; Wolszczak, Marta; Szmit, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Glioblastoma is the most common type of primary cancer in the brain, at the same time being the most aggressive one. In this review, we describe current and emerging strategies for glioblastomas, taking into consideration existing challenges and prospective solutions. State of knowledge: Standard treatment comprises surgery, radiotherapy, and primary and maintenance chemotherapy. Those treatments result in a mean overall survival of around 12 to 15 months. We summarize emerging advancements in the field of gene therapy, immunotherapy, viral (oncolytic) therapies, and anti-angiogenic drugs with a focus on key research findings and clinical trial outcomes. Summary: The unfavorable prognosis for GBM poses a pressing need for more effective treatments, resulting in prolonged progression-free survival and overall survival, but the difficult microenvironment and immunosuppressive abilities of glioblastomas pose a significant challenge for the emerging strategies. Fortunately, ongoing research proposes solutions to overcome these challenges, like convection-enhanced delivery (CED) to overcome the brain blood barrier or more efficient vectors. The most promising therapies are: DCVax-L (dendritic vaccine), CAR-T therapies targeted against IL13Rα2 and EGFRvIII, and oncolytic viruses: G47Δ (DELYTACT) and PVSRIPO. Future advancements in the management of GBM will focus on the combination of multimodal therapies.